Change in psychological control in visually impaired older adults over 2 years: role of functional ability and depressed mood - Schilling, Oliver; Wahl, Hans-Werner; Boerner, Kathrin; Reinhardt, Joann P.; Brennan-Ing, Mark; Horowitz, Amy (The journals of gerontology. Series B, Psychological sciences, social sciences, 2013)
Objectives: The life-span theory of control is applied to study change in vision-specific control strategies in visually impaired older individuals, depending on performance in instrumental activities of daily living (IADL) and depressed mood. Method: Longitudinal data from visually impaired individuals (at baseline: N = 364; mean age = 82.8 years; visual acuity less than 20/60) measured at three occasions with 1-year intervals in-between were analyzed. A newly established vision-specific control scale to assess selective primary control (SPC), selective secondary control (SSC), compensatory primary control (CPC), and compensatory secondary control (CSC) was used. Linear and nonlinear (quadratic and piecewise) generalized mixed models with gamma response distribution to fit the skewed data were applied. Results: CPC progressively increased as IADL capacity decreased up to a turning point, at which CPC plateaued, whereas all other strategies declined linearly with IADL decrease. Controlling for depressed mood did not change these relationships for CPC, SPC, and SSC but absorbed IADL-related decline of CSC. Higher depression was associated with less SPC, SSC, and CSC, but only slightly with less CPC. Discussion: IADL plays an important role triggering a shift in adaptational strategies from selective control to CPC in visually impaired older adults and possibly other disabled populations.
Published: 21 December 2012
Gesehen am 24.06.2021